2006
DOI: 10.1016/j.cmet.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

PERK EIF2AK3 control of pancreatic β cell differentiation and proliferation is required for postnatal glucose homeostasis

Abstract: Mutations in PERK (EIF2AK3) result in permanent neonatal diabetes as well as several other anomalies that underlie the human Wolcott-Rallison syndrome, and these anomalies are mirrored in Perk knockout mice. To identify the cause of diabetes in PERK-deficient mice, we generated a series of tissue- and cell-specific knockouts of the Perk gene and performed a developmental analysis of the progression to overt diabetes. We discovered that PERK is specifically required in the insulin-secreting beta cells during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
273
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 255 publications
(291 citation statements)
references
References 20 publications
12
273
2
4
Order By: Relevance
“…Acute Inhibition of PERK Activity Impairs Glucose-dependent Insulin Secretion-Previously we showed that glucose-stimulated insulin secretion was ablated in islets isolated from neonatal PKO mice (19). In the present study, this result was confirmed by genetic knockdown of Perk in INS1 832/13 ␤-cells bearing a tetracycline-operated shPerk transgene (denoted as INS1 832/13 shPerk cells).…”
Section: Inhibition Of Perk Activity Recapitulates ␤-Cell Dysfunctionssupporting
confidence: 75%
See 3 more Smart Citations
“…Acute Inhibition of PERK Activity Impairs Glucose-dependent Insulin Secretion-Previously we showed that glucose-stimulated insulin secretion was ablated in islets isolated from neonatal PKO mice (19). In the present study, this result was confirmed by genetic knockdown of Perk in INS1 832/13 ␤-cells bearing a tetracycline-operated shPerk transgene (denoted as INS1 832/13 shPerk cells).…”
Section: Inhibition Of Perk Activity Recapitulates ␤-Cell Dysfunctionssupporting
confidence: 75%
“…Seen in Genetic Ablation of Perk-Previously we showed that loss of function mutations of Perk in mice (PKO) led to an impacted ER phenotype in a substantial fraction of ␤-cells (30 -40%) characterized by accumulation of proinsulin and other client proteins in the ER and failure of anterograde trafficking to the Golgi (19,20,27). This phenotype can be readily detected using immunohistochemical labeling of insulin and proinsulin in mouse islets of Langerhans (Fig.…”
Section: Inhibition Of Perk Activity Recapitulates ␤-Cell Dysfunctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few factors, however, have been shown to regulate embryonic β-cell proliferation in vivo. The eIF2α kinase PERK is important for β-cell proliferation in embryos and neonates but not in the adult (14). The transcription factor Pdx-1 is essential for pancreas organogenesis and β-cell proliferation (15)(16)(17).…”
mentioning
confidence: 99%